ANALISIS PERBEDAAN KAPASITAS FUNGSI PARU PADA PEDANGANG KAKI LIMA BERDASARKAN KADAR DEBU TATAL DI JALAN NASIONAL KOTA SEMARANG - Nurjazuli -; Onny Setiani; Elanda Fikri (Universitas Muhammadiyah Semarang, 2010)
Background : Semarang city as the province and industry city have high mobility, which the amount of vehicle increases at rate of 5 to 9 % per year. Vehicles increases in Semarang city have potency for air pollution so that it would have effect to our health. Air pollution occurred caused by transportation would affect lung function suffered by worker around the street, such as cloister merchant. This research aimed to identify difference of lung function capacity on cloister merchant based on totalambient dust level in Semarang City National Street.Methods: This research was an observational research using a cross sectional approach. Analysis unit of this research were 3 National Street in Semarang City (Kaligawe Street, Siliwangi Street, and Perintis Kemerdekaan Street) also 63 cloisters merchant were taken in purposive sampling.Result : Dust concentration data obtained by direct measurement to three Semarang City National Streets (Kaligawe Street= 624,7 μg/m3, Siliwangi Street= 533 μg/m3, Perintis Kemerdekaan Street= 377,2 μg/m3). While, lung function data obtained with examine the lung function of cloister merchant using spirometri (μ %KVP=92,75, SD %KVP=16,861 dan μ %VEP1=99,27, SD %VEP1=19,345 ) and other data obtained by interview. Data analysis performed using one-way Annova (=0,05).The statistic result by one-way Anova performed following result: there was no significant difference of prediction value of %KVP (df=62; p=0,110) and prediction value of %VEP1 (df=62; p=0,829) on cloisters merchant based on total ambient dust level in three Semarang City National Street.Conclusions: Nutrient status, examination habit, homogeneity of respondent, also respondent disease track record may become potential factor in reinforcing pulmonary function disorders. Conclusion there are no statistical difference of respondent’s lung capacity, even though total ambient dust concentration in three Semarang city national street are different.Keywords : Lung function capacity,dust, cloister merchant